2016
DOI: 10.1016/j.juro.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

γ Irradiated Mycobacteria Enhance Survival in Bladder Tumor Bearing Mice Although Less Efficaciously than Live Mycobacteria

Abstract: Our results show that although γ irradiated mycobacteria is less efficacious than live mycobacteria, it induces an antitumor effect in vivo, avoiding the possibility of further mycobacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…We recently demonstrated the antitumor and immunomodulatory activity of this mycobacterium ( 4 , 5 ). In vitro studies have shown the capacity of M. brumae to activate macrophages.…”
Section: Genome Announcementmentioning
confidence: 99%
“…We recently demonstrated the antitumor and immunomodulatory activity of this mycobacterium ( 4 , 5 ). In vitro studies have shown the capacity of M. brumae to activate macrophages.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Between both treatments, γ-irradiated mycobacteria trigger cytokine levels closer to those induced by live mycobacteria, than those induced by HK mycobacteria. Regarding immune activation: induction of cytotoxicity by activated cells, induction of cytokine production, and expression of activation markers on immune cells, again the immune response induced by live mycobacteria was higher than that triggered by non-viable mycobacteria [63,66,70,71].…”
Section: Purified Mycobacteria Antigens and Non-viable Mycobacteriamentioning
confidence: 95%
“…Interestingly, when live BCG or M. brumae was instilled in the first week of treatment and subsequent instillations were done using γ-irradiated mycobacteria, significant prolonged survival rates were observed in tumor-bearing mice compared to untreated mice [71].…”
Section: Purified Mycobacteria Antigens and Non-viable Mycobacteriamentioning
confidence: 99%
“…The idea to inactivate BCG by heat, irradiation, or formaldehyde in order to prevent its side effects due to the living bacteria is already old, but recently was addressed again in preclinical studies. 38 , 39 However, one is far from clinical application. Anyhow, one may expect that, if inactivated BCG keeps its therapeutic effect, the side effects due to the immune response will remain.…”
Section: Prevention Strategies To Diminish Toxicitymentioning
confidence: 99%